Enhancing Inventory Control through Compliance Evaluation of an Android Cashier Application: Meningkatkan Kontrol Persediaan melalui Evaluasi Kepatuhan Aplikasi Kasir Android - Pangerti, Errina Nur Setia Pambudi; abidin, Fityan izza noor (Indonesian Journal of Law and Economics Review, 2024)
This study evaluates an android-based cashier application (Applicationr) at Toko Berkah Abadi in accordance with PSAK No. 14 guidelines for inventory management. Using qualitative descriptive methods including interviews, observation, and documentation, the research finds that the application adequately meets standards for inventory assessment, recording methods, and categorization. However, areas for improvement include implementing a stock book feature for better goods monitoring and setting minimum order thresholds to streamline product ordering. These findings highlight opportunities to enhance the application's effectiveness in controlling merchandise inventory, thereby potentially improving overall business efficiency and regulatory compliance in retail settings. Highlights: Compliance evaluation with PSAK No. 14 for inventory accuracy. Identification of strengths and areas for inventory management enhancement. Improving merchandise control for enhanced retail efficiency and compliance. Keywords: Android-based cashier application, PSAK No. 14, inventory management, qualitative research, retail efficiency